Cross-Sectional Study: The Association between Predisposing Factors and Medication Adherence among Hypertensive Patients - Emanuel Gerald Alan Rahmat; Muhamad Satria Manda Pua Upa; Lely A.V. Kapitan (Ahmar Metastasis Health Journal)
Hypertension is a very high morbidity and mortality worldwide. It has become a serious public health problem in Indonesia and worldwide. East Nusa Tenggara Province is ranked third in terms of hypertension. Kupang City has the highest prevalence in the region. This study aims to determine the association between determinant predisposition variables, namely knowledge and attitudes towards treatment adherence of hypertension patients at primary health care centres in Kupang City, East Nusa Tenggara, Indonesia. This study is a cross-sectional observational study. The data collection instrument uses the MMAS 8 questionnaire sheet, which has been tested for validity and reliability. The sampling technique used was simple random sampling involving 72 respondents. The data was tabulated, analysed descriptively, and tested using the chi-square test using computer application software. The results of the study show that demographically, most of the people with hypertension are in the average age group of 51.80 (SD±3.82), female gender (51.39%), high school education (61.11%), and civil servant occupation (29.17%). The level of knowledge was good (51.39%), the attitude was good (68.06%), and medication adherence was low (87.50%). The results showed no significant association between knowledge (p-value 0.05), attitude (p-value 0.05), and medication adherence.